Leadership of The Head of The Community Learning Center as A Motivator in Community Learning (Case Study on Papua Sejahtera Community Learning Center in Manokwari Regency) - Habib, Muhammad Rafi Iriawan; Ishaq, M. Ishaq; Ahmad, Ahmad (Universitas Negeri Padang, 2024)
This study aims to: (1) analyse the advantages of flexible and innovative leaders, (2) analyse the advantages of leaders who are able to manage and organize, and (3) analyse the advantages of leaders who are able to communicate well in ensuring that information about education programs can be conveyed well to the community. This research uses a qualitative approach with a case study research type. Data collection methods were conducted using interviews, observations and documentation studies. Data analysis was conducted through the stages of data condensation, data display, and verification and conclusion drawing. The data validity test was carried out using the triangulation method. The results showed that: (1) The head of PKBM Papua Sejahtera has adopted a democratic leadership approach that allows for member participation in decision-making, while also demonstrating flexibility and responsibility towards change. The head of PKBM, evident through his responsiveness to behavioral changes and openness to suggestions and inputs, affirms his commitment to adaptive and sustainable learning, especially in the context of implementing an independent curriculum and online and offline learning during the Covid-19 pandemic, (2) The Head of PKBM Papua Sejahtera applies innovative leadership that integrates various leadership theories, including inclusive and collaborative approaches in decision making, wise task delegation strategies, and handling difficult situations with various strategies, (3) Good and effective communication skills possessed by the Head of PKBM Papua Sejahtera are a key element in the successful management of the education unit. His inclusive communication approach, various means of communication used, and consistency in communication ensure that information is conveyed well and on time to the PKBM community. The honest, transparent, trustworthy and understanding attitude shown by the leadership builds a strong foundation of trust, which then opens up space for openness and positive participation from PKBM members. A holistic approach to conveying information, including the use of various media and in-person interaction, helps ensure communication effectiveness, especially in the face of change or uncertainty. Effective communication is a key driver in creating an enabling environment for the growth, participation and successful management of PKBM. Keywords: Leadership, Motivator, Community Learning